Manajemen Pengembangan Guru Dalam Menghadapi Tantangan dan Peluang Di Kurikulum Merdeka - Haratua, Chandra Sagul; Prabayoansa, Aris; Daulay, Lispidar; Tuti, Tuti; Nida, Nida; Fahrizal, Tobi (Peneliti.net, 2023)
Teacher development management to meet the challenges and opportunities of independent curriculum teaching. By assessing the importance of the role of teacher education management in responding to the dynamics of the Merdeka program. These challenges, including adapting to workload and student diversity, require effective management strategies. On the other hand, opportunities such as personalized learning and creativity in teaching offer the potential to improve the quality of education. Through careful developmental management, teachers can maximize the potential of the curriculum, create a responsive learning environment, and prepare students to meet the needs of the future.